RIO GRANDE TURKEY FEMALE SURVIVAL IN SOUTHCENTRAL KANSAS - Randal S. Hennen; Scott Lutz (Wildlife Society Bulletin)
Abstract: We used 127 radiomarked Rio Grande wild turkey (Meleagris gallopavo intermedia) females to estimate survival from March 1994 to March 1996 in Comanche and Clark counties, Kansas. We estimated annual survival was 0.39 and found that it did not vary by age (P = 0.54), year (P = 0.70), female weight class (P = 0.19–0.81), or trap site (P = 0.07–0.58). Female survival was lower during the recruitment period (16 Mar–15 Jul; S = 0.63) than during the postrecruitment period (16 Jul–15 Nov; S = 0.80) or winter (16 Nov–15 Mar; S = 0.79) periods (P < 0.01). Predation accounted for 94% of all mortalities. When we compared survival rates between reproductively active and inactive females, we found that brood‐rearing behavior was associated with low survival in 1 year. The difference in survival rates appeared to be related to above‐average precipitation events during early brood rearing. We suggest that Rio Grande wild turkey populations in these southcentral Kansas counties may be limited by low female survival during the recruitment period. Because Rio Grande turkeys in these Kansas counties exist at the edge of their geographic range and recruitment appears vulnerable to stochastic weather events, and demographic rates are relatively low, we believe managers should conservatively manage these populations.